Does Digital Finance Reduce Cash Holdings? Evidence on Money Demand in ASEAN - Nala Syifa Dewanti; Cinta Laura Nurhan; Alfaina Zia Inayati (EkBis: Jurnal Ekonomi dan Bisnis, 2025)
This study investigates the impact of digital finance, alongside globalization and exchange rates, on money demand in six ASEAN countries (Indonesia, Malaysia, Singapore, Thailand, Philippines, and Vietnam) from 2015-2023. The primary purpose is to analyze how digital financial transformation influences cash holdings and monetary stability in a developing regional context, an area with limited empirical evidence. Utilizing a panel data regression approach with fixed effects model estimation, the research employs indicators suc as ATM density, mobile subscriptions, internet penetration, the KOF Globalization index, and official exchange rates. The main findings remain dominant drivers: ATM access and globalization have positive effects on broad money demand. However, a composite Digital Financial Inclusion Index consolidating digital variables exhibits a strong positive significant effect, digital advancements holistically strengthen financial deepening. The study contributes to monetary economics by highlighting the complex, evolving nexus between digitalization and money demand in emerging economies.